ANALISIS PERENCANAAN AGREGAT PADA CV. SUMBER REZEKI DI SAMARINDA - -, Dede Mariyani (EKONOMIA, 2014)
This study on the CV. Sumber Rezeki is one company whose main activity is the manufacture of tile . Tile that is used as one important component in the settlement , this time has been much needed by the consumer . Plus the development of business - residential construction or real estate settlement which means activity is also increasing use of tile . Therefore CV. Sumber Rezeki always trying to improve its business in accordance with the pace and level of development today to meet market demand . Based on the above , it can be a problem in this study is :